2022
DOI: 10.1017/s0140525x2200005x
|View full text |Cite
|
Sign up to set email alerts
|

Rational framing effects: A multidisciplinary case

Abstract: Frames and framing make one dimension of a decision problem particularly salient. In the simplest case, frames prime responses (as in, e.g., the Asian Disease paradigm, where the gain frame primes risk-aversion and the loss frame primes risk-seeking). But in more complicated situations frames can function reflectively, by making salient particular reason-giving aspects of a thing, outcome, or action. For Shakespeare's Macbeth, for example, his feudal commitments are salient in one frame, while downplayed in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 293 publications
0
2
0
Order By: Relevance
“…The study found that concrete analogies are simpler to understand than abstract ones. In hedonic product advertising, recessive metaphors outperform dominant metaphors, according to research by Bermúdez [ 6 ], although practical product promotions yielded the reverse findings. Therefore, selecting appropriate metaphor types and adjusting them to various product types and consumers’ cognitive needs can aid product designers in increasing their goods’ appeal and communication efficacy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study found that concrete analogies are simpler to understand than abstract ones. In hedonic product advertising, recessive metaphors outperform dominant metaphors, according to research by Bermúdez [ 6 ], although practical product promotions yielded the reverse findings. Therefore, selecting appropriate metaphor types and adjusting them to various product types and consumers’ cognitive needs can aid product designers in increasing their goods’ appeal and communication efficacy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Often thought of as an instance of irrationality (how could it be rational to value one and the same thing depending simply on the perspective one takes on it? ), this effect has lately been discussed by philosophers who want to question whether it really is always normatively problematic (Bermúdez forthcoming, Paul forthcoming).…”
Section: A Matter Of Perspectivementioning
confidence: 99%